Progress in the modification of reverse osmosis (RO) membranes for enhanced performance - Otitoju T.A.; Saari R.A.; Ahmad A.L. (Korean Society of Industrial Engineering Chemistry, 2024)
Indexed by WOS/SCOPUS/ERA